2017
DOI: 10.1051/0004-6361/201629907
|View full text |Cite
|
Sign up to set email alerts
|

Resolved magnetic structures in the disk-halo interface of NGC 628

Abstract: Context. Magnetic fields are essential to fully understand the interstellar medium and its role in the disk-halo interface of galaxies is still poorly understood. Star formation is known to expel hot gas vertically into the halo and these outflows have important consequences for mean-field dynamo theory in that they can be efficient in removing magnetic helicity. Aims. We aim to probe the vertical magnetic field and enhance our understanding of the disk-halo interaction of galaxies. Studying a face-on galaxy i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 92 publications
(200 reference statements)
2
58
2
Order By: Relevance
“…The largest difference is found in M 31. For individual magnetic arms, p o was found to be larger than p s by about 20 • in M 83 [173], about 8 • in M 101 [174], and 12 • − 23 • for the three main arms in M 74 [171]. This could indicate that anisotropic turbulent fields, responsible for a significant fraction of the polarized emission, have a systematically larger pitch angle than the regular field.…”
Section: Galaxymentioning
confidence: 90%
“…The largest difference is found in M 31. For individual magnetic arms, p o was found to be larger than p s by about 20 • in M 83 [173], about 8 • in M 101 [174], and 12 • − 23 • for the three main arms in M 74 [171]. This could indicate that anisotropic turbulent fields, responsible for a significant fraction of the polarized emission, have a systematically larger pitch angle than the regular field.…”
Section: Galaxymentioning
confidence: 90%
“…Similar results have been seen in the disk of the face-on galaxy, NGC 628, as shown in Figs. 18 and 26 of Mulcahy et al (2017) and also more recently in the disk of the edge-on galaxy, NGC 4666 (Stein et al 2019). For the latter galaxy, the field direction also flips across the major axis of the galaxy.…”
Section: Introductionmentioning
confidence: 94%
“…However it is becoming common place to give the Faraday depth by RM synthesis for nearly face-on galaxies (e.g. Beck 2015b; Mulcahy et al 2017). Thus in this section we give a preliminary RM screen analysis of essentially the same model used in the previous section.…”
Section: Rm Screen For Face-on Galaxiesmentioning
confidence: 99%
“…On the other hand, we take B coh as a free parameter, varying its value to see the effects on the Faraday spectrum. Recent RM studies of face-on external galaxies such as IC 342 (Beck 2009) and NGC 628 (Mulcahy et al 2017) indicated absolute values of the RM up to ∼100 rad m −2 , which corresponds to up to ∼6 μG if we assume that the average thermal electron density along the LOS is 0.02 cm −3 and the path length through the thermal gas is 1 kpc. So, we set B coh = 0-5 μG.…”
mentioning
confidence: 96%